The Value of Family and Friendship Ties and Their Effect on Providing Funding for Millennial Entrepreneurs - Ika Yoga; Retnoning Ambarwati (Profesional Muda Cendekia Publishing, 2023)
Providing financing for entrepreneurs becomes an interesting topic to discuss in relation to the financial literature, especially in the financial literature of small and medium enterprises. The purpose of this study is to investigate the value of family and friendship ties in financing millennial entrepreneurs. This study will focus on analyzing the level of support and financial assistance millennial entrepreneurs receive from their family and friends. In addition, this study will examine the factors that influence family and friends' decision to finance millennial entrepreneurial ventures. The research will be conducted through surveys and in-depth interviews with millennial entrepreneurs and their funder family and friends. The findings of this research will provide valuable insights into the importance of human relationships in the entrepreneurial ecosystem and inform future support programs for young entrepreneurs. The data used in this study are the results of a questionnaire given to small and medium business actors in the ex-residency area of Surakarta. The method used in this research is the method of SEM-PLS. The finding of multiple regression analysis techniques reveals that e value of family ties and the value of friendship had a significant influence on providing funding for entrepreneurs. These findings suggest that young entrepreneurs should pay attention to and be able to build strong relationships with their family and friends in the hope that these relationships can play an important role in securing funding for their business. The next research is expected to be able to study more deeply about its effect on the surplus value obtained compared to unrelated third party financing